2014
DOI: 10.1177/0022185614523277
|View full text |Cite
|
Sign up to set email alerts
|

The monitoring and enforcement of labour standards when services are contracted out

Abstract: This article demonstrates that by contracting-out government services, the employment relationship has changed: workers' labour standards are now regulated through the combination of traditional labour law mechanisms and lesser understood contract law mechanisms. This has changed the regime of regulation and enforcement of labour standards for employees performing services that have been contracted out, in ways that deserve more attention. Evidence is drawn from a case study of New South Wales (NSW) government… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…(p. 34) As consumers of goods and services in many sectors, the state could leverage its power to enhance and protect labour standards from its suppliers. The concept of government being in the position of lead supplier is alluded to in Holley's (2014) discussion of the changing role of governments in public procurement. Indeed, Holley (2014) argues that government has defaulted in its role as 'regulator' and in doing so has changed to 'contractor' of public services.…”
Section: The Role Of the Statementioning
confidence: 99%
See 3 more Smart Citations
“…(p. 34) As consumers of goods and services in many sectors, the state could leverage its power to enhance and protect labour standards from its suppliers. The concept of government being in the position of lead supplier is alluded to in Holley's (2014) discussion of the changing role of governments in public procurement. Indeed, Holley (2014) argues that government has defaulted in its role as 'regulator' and in doing so has changed to 'contractor' of public services.…”
Section: The Role Of the Statementioning
confidence: 99%
“…This neoliberal shift (Anderson and Quinlan, 2008;Markey, 2008) has been remarked on elsewhere as part of a shift to new public management where business trumps the 'public sector ethos' of the public service (Hebson et al, 2003: 482). Tendering processes have thus focussed more on presumptions of contractual processes as vehicles for efficiency rather than enhanced labour standards (Holley, 2014;. This poses problems for the inclusion of 'social aims' in publicly funded supply chains.…”
Section: The Role Of the Statementioning
confidence: 99%
See 2 more Smart Citations
“…Research on contracting out and public contracting of services has suggested that these developments have important implications for working conditions and the quality of services (Benjamin, ; Dube & Kaplan, ; Engström & Axelsson, ; Flecker & Hermann, ; Grimshaw, Cartwright, Keizer, & Rubery, ; Vrangbæk, Petersen, & Hjelmar, ). With the growing importance of public contracting, public contracts increasingly act as tools for defining standards of services (Lahat & Talit, , p. 336) and regulating labour standards and working conditions (Holley, ). Yet, despite their importance as a regulatory tool, little is known about public authorities' strategies to warrant decent working conditions and a high quality of services when tendering.…”
Section: Introductionmentioning
confidence: 99%